Reconstructing paleohydrology in the northwest Great Basin since the last deglaciation using Paisley Caves fish remains (Oregon, U.S.A.). (15th June 2021) - Hudson, Adam M.; Emery-Wetherell, Meaghan M.; Lubinski, Patrick M.; Butler, Virginia L.; Grimstead, Deanna N.; Jenkins, Dennis L.
Abstract: The arid northwest Great Basin underwent substantial hydroclimate changes in the past 15, 000 years, greatly affecting its desert ecosystems and prehistoric people. There are conflicting interpretations of the timing of hydrologic changes in this region, requiring more records to resolve the dominant climatic drivers. The Paisley Caves archaeological site, located near former pluvial Lake Chewaucan, contains well-dated, stratified sediments best known for evidence of early human occupation in North America. We present a novel paleohydrologic record for the Chewaucan basin based on the frequency of fish remains (Salmonidae and Cypriniformes, likely tui chub) and their carbon, oxygen, and strontium isotope compositions, from the Paisley Caves. Cypriniformes abundance peaks first at the start of the Bølling/Allerød warm interval (∼14.7 ka) and again during the early Younger Dryas (∼12.8 ka). Isotope compositions indicate tui chub were derived from an expansive Lake Chewaucan throughout the Bølling/Allerød, but mainly from spring- or stream-influenced sources by the late Younger Dryas to the present. Fish abundance dropped sharply through the Younger Dryas and early Holocene, when isotope compositions indicate a mix of habitats. Isotope compositions indicate the driest conditions during the middle Holocene, followed by slightly wetter conditions up to the present. This record agrees with recent pluvial lake reconstructions, supporting the hypothesis that a northward shift in the winter storm track supported deep lakes throughout the Bølling/Allerød in the northwest Great Basin. Lake level decline during the Younger Dryas suggests drying climate, differing from more southerly records. During the Holocene, however, shifts in Chewaucan basin hydrology are consistent with the rest of the western U.S. This highlights the need for region-specific records to inform predictions of the hydrologic impact of climate change on arid regions. Highlights: We create a 15 kyr age-depth model for parts of Paisley Caves 2 and 5, Oregon, USA. Abundance and isotopes of fish remains in the caves record past hydrologic change. Tui chub thrived in pluvial Lake Chewaucan throughout the Bølling/Allerød. Lake decline forced chub into fresher habitats from Younger Dryas to present.